Case report of a young girl with persistent hyperplastic primary vitreous and psychosis - Wong, Daniel Teck Lung; Masiran, Ruziana; Wan Ismail, Wan Salwina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Childhood- and adolescent-onset schizophrenia are rare. Along with positive, negative, affective and cognitive symptoms, eye-tracking dysfunction characterized by a disturbance in the smooth pursuit system has been the only associated visual impairment found in schizophrenia. This case report highlights a case of a child with persistent hyperplastic primary vitreous who had gradual onset of psychosis over two years duration. A final diagnosis of schizophrenia was considered and she was started on antipsychotics, to which she showed gradual response with mild extrapyramidal side effects.